Evaluation of mammographic density and Tc-99m-sestamibi scintimammographic uptake in postmenopausal women on hormone replacement therapy - Nahas-Neto, J.; De Luca, L. A.; Griva, B. L.; Morceli, J.; Nahas, EAP; Moriguchi, S. M.; Uemura, G.; Traiman, P. (Elsevier B.V., 2006)
Objective: To evaluate changes in mammographic density and Tc-99m-sestamibi scintimammographic uptake in postmenopausal women on hormone replacement therapy (HRT).Methods: Seventy-five postmenopausal women were prospectively studied and allocated into three groups: 50 women were randomized to either Group 1 (G1, n = 25), which received 2 mg of 17 beta-oestradiol continuously combined with 1 mg of norethisterone acetate (E-2/NETA, Kliogest (R), Medley) or Group 2 (G2), which received 2.5 mg/day of tibolone (Livial (R), Organon). The remaining 25 women, who were asymptomatic and had no desire to undergo HRT, constituted the control group (G3). Each patient was submitted to both mammography and scintimammography at baseline and after six months. Mammographic density was evaluated by using the BI-RADS classification system. The classification system of Barros et al. was used in the interpretation of scintimammography. For statistical analysis, the Chi-square test, ANOVA and Pearson's correlation were used.Results: At six months, increased mammographic density was observed in 48% of G1, 12% of G2 and 16% of G3 patients (p < 0.001). The increase in sestamibi uptake was 56% in G1, 28% in G2 and 24% in G3 (p < 0.001). Increases in both density and uptake were significantly higher in the group on E-2/NETA than among tibolone users and the controls.Conclusion: In postmenopausal women, HRT with E-2/NETA was associated with increased mammographic density and increased Tc-99m-sestamibi scintimammographic uptakes, suggesting greater mithochondrial activity in the cells of the mammary duct. This was not observed in users of 2.5 mg of tibolone, demonstrating that the effects on the breast were reduced. The same was observed in the control group. (c) 2005 Elsevier B.V.. All rights reserved.
Keywords: menopause; scintimammography; mammographic density; hormone replacement therapy; tibolone